GUIDANCE ON IMPLEMENTATION OF ACHIEVING FITNESS LEVEL IN FIT CLUB SIMPANG D RAMBAH JAYA KECEMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Siska; Debby Indah (Lembaga Penelitian dan Pengabdian Masyarakat STKIP Rokania, 2020)
Low understanding of gymnastics members in improving fitness, so the solution is given as follows: 1) Introducing aerobic exercise, 2) Introducing anaerobic exercise, 3) Introducing the principles in the exercise program and 4) Helping to introduce the key to successful training.The method used is Training of Trainer (TOT) with lectures and direct previews. Physical fitness is a person's condition at any given time. A person's physical fitness condition is not permanent, but the quality rises because of regular exercise and will descend if not. In principle to improve physical fitness need to pay attention to the following things: 1) Aerobic exercise exercises such as jogging, fast walking, swimming, cycling, and aerobic gymnastics. 2) do fitness exercises and muscle tightening (anaerobic) to improve the quality of strength, speed, Kelentukan, power, and so on, 3) understand the principles of fitness exercises such as overload (load more), specifics (specificity), Riversible (back origin), 4) keys to a successful exercise. Success will be tested if the exercise is regular, increasing the intensity of the exercises gradually, nutrition and istirahap are adequate and maintain a positive attitude. The odds are; 1) Improve the understanding and skill of gymnastics members to be able to see the level of physical fitness, principles in exercise programs and exercise forms and, 2) produce scientific publications in the journal National Devotion not accredited